Determinants of immunization coverage among 12-23 months children: A study from Haryana - Bhonsla, Suresh Kumar; Bhardwaj, Anu; Mittal, Anshu; Singla, Gagan; Garg, Shalu; Rani, Sujata (Indian Journal of Community Health, 2019)
Background: Immunization is safe, powerful and proven tool for elimination and controlling various highly infectious diseases and in spite of every possible effort put by the Government still there is a big gap between reported and evaluated coverage. Aims & Objectives: To find out the immunization coverage and its determinants among children in the age group 12 – 23 months in urban and rural area of district Ambala. Material and Methods: It was a cross sectional study carried out by WHO recommended 30 by 7 cluster survey technique. Results: It was observed that overall 83.1% children were fully immunized, 14% were partially immunized and 2.9% were unimmunized. In present study Educational status of mothers, Occupation of mothers, Religion, Sex, Monthly Family Income and Caste were found to be significantly associated with immunization coverage. “Fear of side effects” of vaccination was found to be the main reason for failure to fully immunize the child. Conclusion: To conclude, immunization coverage was found to be reasonably but still there is a lot of scope for improvement.